Pengaruh Harga, Promotion, Electronic Word Of Mouth Terhadap Keputusan Pembelian Konsumen Pada E-Commerce Shopee (Studi Pada Mahasiswa Universitas Islam Malang Angkatan 2021) - Setyowati, Kiki; Rachma, N; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to determine and analyze the relationship between the influence of price, promotion, and electronic word of mouth on consumer purchasing decisions on the Shopee e-commerce platform. This study uses a case study of students from the University of Islam Malang, class of 2021, where data was collected through the distribution of a questionnaire via Google Forms to randomly selected students from the University of Islam Malang, class of 2021. The sample size was determined using Malhotra's formula, resulting in 96 respondents. The data analysis method used in this study was data processing using the IBM SPSS 26 program. The results of this study indicate that price, promotion, and electronic word of mouth simultaneously influence purchasing decisions. Partially, price has a positive influence on purchasing decisions, promotion has an influence on purchasing decisions, and electronic word of mouth has the most dominant influence on purchasing decisions. Keywords: Price, Promotion, Electronic Word of Mouth, Purchase Decision